Near-infrared rechargeable glass-based composites for green persistent luminescence - Arango N.G.; Vuori S.; Byron H.; Van der Heggen D.; Smet P.F.; Lastusaari M.; Petit L. (Elsevier Ltd, 2022)
The fabrication of Yb3+, Tm3+ co-doped oxyfluorophosphate glass-based composites, with green persistent luminescence after being charged with near-infrared light, is demonstrated. The mechanism responsible for the green afterglow after near-infrared illumination is unveiled. The composite is prepared using a modified melting process to limit the evaporation of fluorine during melting. Intense (blue and ultraviolet) up-conversion emission is obtained by optimizing the Yb2O3 and Tm2O3 concentrations. A heat treatment promotes volume precipitation of Yb3+, Tm3+ co-doped CaF2 crystals. Although the intensity of the blue up-conversion emission from the Tm3+ 1G4 level is lower in the highly Yb3+-concentrated glass-ceramic due to reverse energy transfer from Tm3+ to Yb3+, the heat treatment leads to an increase of the intensity of the emissions around 346 nm, 361 nm nm and 450 nm coming from the Tm3+ 1I6 and 1D2 levels. By combining the Yb3+ and Tm3+ ions with SrAl2O4:Eu2+,Dy3+crystals, green afterglow can be obtained after charging with near-infrared light.